The Relationship Between Years of Service and Traumatic Experiences Related to Radiation Among Local Government Staff Working Within 30 km of the Fukushima Daiichi Nuclear Power Station - Matsunaga, Hitomi; Kashiwazaki, Yuya; Orita, Makiko; Xiao, Xu; Takamura, Noboru (Journal of disaster research, 2024)
An accident occurred at Tokyo Electric Power Company’s Fukushima Daiichi Nuclear Power Station (FDNPS) in March 2011, following an earthquake and tsunami. Local government staff members who worked in the area had a variety of experiences due to the accident, including trauma. This cross-sectional study was conducted to clarify the relationship between years of service and radiation-related traumatic experiences among 490 staff members in municipalities around the FDNPS exactly a decade after the accident. They were classified as <5 years, 5–10 years, and >10 years, relative to their lengths of employment. The experienced staff (>10 years of service) had a rich array of traumatic experiences, compared to those with less experience (<5 years of service). By contrast, the experienced staff had a lower SOC-13 score than those with less experience, and a higher percentage of them reported that their workload was greater than that imposed on other local government employees. The study results suggested that the experienced staff members who worked in the affected towns prior to the FDNPS accident have been burdened with a prolonged heavier workload, including radiation-related duties.